In vitro Plant Regeneration of Four Local Varieties of Chickpea (Cicer arietinum L.) Grown in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2011)
In vitro regeneration system was developed through direct organogenesis from decapitated mature embryo explants of locally grown four chickpea varieties, namely, Barichhola-4, Hyprochhola, Binachhola-3 and Binachhola-4. Best response towards multiple shoot regeneration was obtained on MS medium supplemented with 0.5 mg/l BAP, 0.5 mg/l Kn, 0.2 mg/l NAA along with double concentrations of CaCl2 and NH4NO3. However good shoot health and expanded leaf was found on MS medium containing 1.0 mg/l kn. Apart from this, few experiments were conducted with decapitated embryo attached cotyledon. Using this explants highest number of multiple shoots were obtained on MSB medium containing 4× micronutrients of MS medium with 3.0 mg/l BAP and 0.04 mg/l NAA in all four varieties. Shoots regenerated on 1.0 mg/l kn supplemented medium showed good response towards rooting on MS medium supplemented with 0.2 mg/l IBA in all four varieties. It was observed that micrografting is an alternative technique to in vitro rooting in chickpea. Key words: In vitro regeneration; Decapitated embryo; Chickpea. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9047 BJSIR 2011; 46(3): 379-384